2005
DOI: 10.1149/1.1824037
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Lattice Instability as a Capacity Fading Mechanism for 5 V Cathode Materials

Abstract: The origin of the overcharge in the 5 V region observed in lithium-substituted LiM x Mn 2Ϫx O 4ϩ␦ spinels (M ϭ Cr, Ni, Cu; x Ϸ 0.2) prepared at 500°C was analyzed by using accurate analytical spectroscopic techniques ͑mass spectroscopy, nuclear magnetic resonance͒ to examine the electrolyte behavior. The spectra revealed organic solvents to be stable as no decomposition products were detected, thus excluding the electrolyte oxidation as a side reaction accounting for the cell overcharge. However, these spinels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…They attributed these redox peaks at about 4.9 V vs. Li/Li + to decomposition of the electrolyte. Caballero et al observed an oxidation peak at about 5.1 V and ascribed this peak to the release of oxygen from the spinel framework [72]. According to previous studies [9,17,24,73], the features of the obtained cyclic voltammogram indicates that the as-prepared LNMO exhibited dominantly the disordered structure, which is in accordance to the SAED result.…”
Section: Resultssupporting
confidence: 83%
“…They attributed these redox peaks at about 4.9 V vs. Li/Li + to decomposition of the electrolyte. Caballero et al observed an oxidation peak at about 5.1 V and ascribed this peak to the release of oxygen from the spinel framework [72]. According to previous studies [9,17,24,73], the features of the obtained cyclic voltammogram indicates that the as-prepared LNMO exhibited dominantly the disordered structure, which is in accordance to the SAED result.…”
Section: Resultssupporting
confidence: 83%
“…The presence of impurities such as traces of organic components seems to play a minor role here. The unresolved peak above 4.8 V, which was specially significant for the PEG 400 sample but barely visible for the PEG 800 sample, can be assigned to either electrolyte oxidation [40] or release of oxygen from the spinel lattice. [41] The electrochemical performance of the two spinels was assessed from galvanostatic measurements made over a wide range of charge/discharge rates (from C/4 to 15C, where C represents 1 Li + ion exchanged in 1 h equivalent to 148 mA g -1 ) and cycling over the voltage range 3.5-5.0 V. Figure 7 shows the variation of the discharge capacity of the two spinels obtained from the PEG-based synthesis recorded at two rates, C/4 and 4C, as a function of cycle number.…”
Section: Full Papermentioning
confidence: 97%
“…The coulombic efficiency of the electrode made from the spinel obtained in the absence of PEG is also included for comparison. The first four cycles were excluded owing to the overcharge introduced by the charging process as the potential result of some oxygen being released above 4.8 V [40] and/or electrolyte oxidation. [41] Although most values exceeded 95 %-which suggests good coulombic efficiency of both electrodes-there were small differences that are worth some comment.…”
Section: Full Papermentioning
confidence: 99%
“…21 The Cu spinels, particularly sample Cu-800, exhibit the most marked differences between experimental and theoretical values. One salient feature is the good consistency between the experimental capacity and the content in Cu 2ϩ at octahedral positions; this suggests that Cu 2ϩ ions at tetrahedral positions are electrochemically inactive below 5.0 V regardless of their origin.…”
Section: Resultsmentioning
confidence: 97%